PENINGKATAN SKILL KADER SEBAGAI UJUNG TOMBAK BIDAN DALAM PELAYANAN KESEHATAN IBU POST PARTUMTENTANG SUGESTI AFIRMASI POSITIF OXCITOSIN MASSAGE - Sari, Ponco Indah Arista; Kusumaningrum, Andri Tri; Putri, Aulia Kurnianing (MAJU : Indonesian Journal of Community Empowerment, 2025)
Health cadres are partners of midwives in providing services to postpartum mothers. The low level of cadres’ skills in practicing oxytocin massage and positive affirmation suggestions may hinder the optimization of postpartum maternal health services. This community service activity aimed to improve the knowledge and skills of cadres in delivering postpartum health care through education and training on oxytocin massage accompanied by positive affirmations. The implementation methods included counseling, demonstrations, hands-on practice, and evaluation using pre-test and post-test among 15 cadres in Geger Village, Lamongan Regency. The results showed a significant increase in the average knowledge score of cadres from 61.5 to 90.5. Practical skills in performing oxytocin massage with positive affirmations also improved, with 90% of cadres able to carry out the technique according to the standard. In conclusion, this program successfully enhanced cadres’ skills, thereby strengthening their role as the front line of midwives in providing postpartum health services.